2020
DOI: 10.1155/2020/4793125
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin Gallate Effectively Affects Senescence and Anti-SASP via SIRT3 in 3T3-L1 Preadipocytes in Comparison with Other Bioactive Substances

Abstract: Aim. We investigated different bioactive compounds including epigallocatechin gallate (EGCG), anthocyanidin, resveratrol, phloretin, spermidine, butyrate, and β-hydroxybutyrate with regard to their effect on SIRT3 via NRF2 and modulation of the proinflammatory senescence-associated secretory phenotype (SASP) in senescence induced 3T3-L1 preadipocytes. Methods. For induction of senescence, 3T3-L1 preadipocytes were incubated with bromodeoxyuridine (BrdU) for 8 days. Cell cycle inhibition was observed, and β-gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…SIRT1 is the most intensively studied member of the SIRT family and it is associated with longevity in animal models. AMPK and SIRT1 both regulate each other’s activities and share many common targets and functions [ 13 , 14 ]. Both AMPK and SIRT promote mitochondrial biogenesis and functioning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SIRT1 is the most intensively studied member of the SIRT family and it is associated with longevity in animal models. AMPK and SIRT1 both regulate each other’s activities and share many common targets and functions [ 13 , 14 ]. Both AMPK and SIRT promote mitochondrial biogenesis and functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Both AMPK and SIRT promote mitochondrial biogenesis and functioning. Consequently, they increase cells ability to generate ATP, diminish oxidative stress, and other potentially adverse cellular events [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…SCFAs, especially butyrate, can regulate the sirtuin deacetylase SIRT1, which plays an important role in the regulation of mitochondrial biogenesis, metabolism, stress responses, genome stability, and aging [112,141]. Resveratrol has been shown, by enhancing the SIRT1 activity, to ameliorate metabolic syndrome [113] (Table 3).…”
Section: Modulation Of Intestinal Homeostasismentioning
confidence: 99%
“…Lilja, Haslberger et al [ 68 ] recently found a senolytic activity of EGCG in 3T3 pre adipocytes, when targeting SIRT3, an important senolytic factor that can regulate ROS-activity via different pathways.…”
Section: Egcgmentioning
confidence: 99%